Improving Scholarship in a Community Hospital Residency Program With a Curriculum Featuring a Structured Roadmap, Individual Accountability, and Measurement of Outcomes - Abdul Waheed; Shehar Bano Awais; Faiza Butt; Hamna Salimi; Zain Elabideen; Muhammad Ali Chaudhary; Mudasir Umer; Erum Azhar (Journal of Medical Education and Curricular Development)
Introduction The Accreditation Council of Graduate Medical Education requires all Graduate Medical Education programs to show evidence of scholarly activity. Fulfilling this obligation remains a challenge for residency programs and remains a common citation by the specialty Residency Review Committees, especially in community hospital settings with limited academic resources. This study evaluated the impact of implementing a bundled intervention on resident scholarly activity within a family medicine residency program in a community hospital. Methods This study employed a quasiexperimental pre- and postdesign to assess the impact of a multifaceted bundled intervention. The scholarly output of residents graduating between 2016 and 2018 (preintervention) was compared to those graduating from 2019 to 2021 (postintervention). Statistical Process Control charts with JMP Pro 17.0 were used to display data and perform phase analysis. Fisher's exact test and the chi-square test were used to compare the demographics, while the Mann-Whitney U -test and one-way analysis of variance were also used to detect the difference in scholarly output between the 2 groups. Results Thirty-one family medicine residents graduated from the program in the study period. A significant increase in the average number of scholarly activities, including all manuscripts and presentations, was noted. The average number of all-scholarly activities increased 4-fold postintervention ( P  < .001). The increase in all-presentations and all-manuscripts was also statistically significant postintervention ( P  < .001 and .0038, respectively). Conclusions Implementing a multifaceted bundled intervention containing a 13-step structured roadmap with a quality improvement approach is associated with increasing residents’ scholarly output in residency programs at a community hospital.